ENGLISH LANGUAGE INSTRUCTION WITH DUOLINGO - Sh.Ismoilova; Xujaxonov Azizbek (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
The function of Duolingo as an online resource for English language instruction is examined in this article.  Through observational and literature-based analysis, it examines the platform's teaching technique, learner engagement, benefits, and drawbacks.  According to the research, Duolingo works well for learning vocabulary and the fundamentals of grammar, but not so well for more complex language skills that call for social engagement.